Pricing Promotion and Online Reviews Drive Customer Loyalty at Mie Gacoan Restaurants in Surabaya : Promosi Harga dan Ulasan Online Mendorong Loyalitas Pelanggan Restoran Mie Gacoan di Surabaya - Khasanah, Dewi; Waluyo, Minto (Academia Open, 2026)
General Background The food and beverage industry is experiencing rapid expansion, intensifying competition and necessitating a deeper understanding of consumer behavior in culinary markets. Specific Background This study examines how the marketing mix (product, price, place, promotion) and electronic word of mouth (e-WOM) relate to purchase intention, purchase decision, repurchase, and customer loyalty within a single integrated framework. Knowledge Gap Prior studies present inconsistent findings and often analyze relationships partially, with limited attention to the sequential process from purchase intention to loyalty. Aims This research aims to analyze the simultaneous relationships among marketing mix variables and e-WOM toward consumer behavioral stages culminating in loyalty. Results The findings indicate that price, promotion, and e-WOM significantly and positively relate to purchase intention, while product and place do not show significant relationships. Purchase intention significantly relates to purchase decisions, which subsequently relate to repurchase behavior and ultimately to customer loyalty. Novelty This study proposes an integrated structural model linking marketing mix and e-WOM to a full behavioral pathway from intention to loyalty using Structural Equation Modeling. Implications The results highlight the central role of pricing strategy, promotional activities, and online reviews in shaping consumer behavior and sustaining long-term loyalty in the culinary sector. Highlights: Significant drivers of purchase intention originate from pricing, promotional activities, and online reviews. Consumer behavior progresses sequentially from intention to decision, then repeat transactions and retention. Product attributes and distribution aspects show limited contribution within the modeled relationships. Keywords: Consumer Behavior, E-WOM, Marketing Mix